Photoredox catalysis harvesting multiple photon or electrochemical energies - Lepori, Mattia; Schmid, Simon; Barham, Joshua P. (Beilstein Journal of Organic Chemistry, 2023)
Photoredox catalysis (PRC) is a cutting-edge frontier for single electron-transfer (SET) reactions, enabling the generation of reactive intermediates for both oxidative and reductive processes via photon activation of a catalyst. Although this represents a significant step towards chemoselective and, more generally, sustainable chemistry, its efficacy is limited by the energy of visible light photons. Nowadays, excellent alternative conditions are available to overcome these limitations, harvesting two different but correlated concepts: the use of multi-photon processes such as consecutive photoinduced electron transfer (conPET) and the combination of photo- and electrochemistry in synthetic photoelectrochemistry (PEC). Herein, we review the most recent contributions to these fields in both oxidative and reductive activations of organic functional groups. New opportunities for organic chemists are captured, such as selective reactions employing super-oxidants and super-reductants to engage unactivated chemical feedstocks, and scalability up to gram scales in continuous flow. This review provides comparisons between the two techniques (multi-photon photoredox catalysis and PEC) to help the reader to fully understand their similarities, differences and potential applications and to therefore choose which method is the most appropriate for a given reaction, scale and purpose of a project.
Keywords: consecutive photoinduced electron transfer; electro-activated photoredox catalysis; photoelectrochemistry; photoredox catalysis; radical ions